A fluorometric assay for tyrosinase activity and its inhibitor screening based on graphene quantum dots. Issue 76 (1st August 2016) - Zhao, X. E.; Lei, C. H.; Wang, Y. H.; Qu, F.; Zhu, S. Y.; Wang, H.; You, J. M.
Abstract : Pristine graphene quantum dots (GQDs) without any functionalization were used as probes to develop a sensitive and selective fluorescence sensing platform for the detection of tyrosinase (TYR) activity and its inhibitor screening for the first time. Abstract : In this work, a sensitive and selective fluorescence sensing platform was developed for the detection of tyrosinase (TYR) activity and its inhibitor screening using graphene quantum dots (GQDs) as probes. Upon excitation at 383 nm, GQDs displayed an intense emission at 445 nm. TYR, a typical polyphenol oxidase, can catalyze the oxidation of dopamine (DA) to dopaquinone and then a fluorescence resonance energy transfer (FRET) process between GQDs and dopaquinone took place. Therefore, the fluorescence of GQDs could be quenched. Thus, quantitative evaluation of TYR activity was established in terms of the relationship between fluorescence quenching efficiency and TYR activity. A linear range was obtained from 0.005 to 0.5 U mL −1 and from 0.5 to 5.0 U mL −1, respectively. A detection limit of 0.0015 U mL −1 was obtained, which was lower than those of reported papers. In addition, it constructed a useful platform for TYR inhibitor screening.